Ranking the freedom in Islam مكانة الحرية في الإسلام - Fauzi, Yusoh; Mohamed Fathy, Mohamed Abdelgelil; Mohammed Saleh, Abdulhadi Ahmed (2019)
Freedom is a key principle and value in the religion of Islam. Islam confirms freedom and spreads it among Muslims. However, in the modern era, freedom is adopted and used against Islam and Muslims. Under freedom of belief, they encourage people to convert and leave Islam. Freedom of expression is used to insult religions and Allah (the Almight). While they propagate freedom of woman to make Muslim woman another version of the Western woman. This is the problem that the paper examines. The paper aims to highlight the concept of freedom and position it at the right place. The paper executes the analytical approach by examines the Quranic texts and the Hadeeths of the prophet Mohammed (P.B.U.H). The researcher concludes the significance of freedom in Islam and how Islam predetermined others in confirming the freedom as one of the Islamic fundamental principle. The findings demonstrate the high ranking of freedom among Islamic principles as shown in the Quranic verses and Hadeeths.